The secrets of success in coaching : 12 ways to excel as a coach - Cope, Mick. (Harlow, England ; New York : Prentice Hall Business/Pearson, 2010)
This text seeks to demystify and open up the coaching practise and provide tried, tested and solid ways for any coach to develop their skills. It presents essential core skills, plain facts and essential tips, tricks and advice all learnt from years of experience.
Secrets of Success in Coaching will bring a breath of fresh air to a subject dominated by case-driven and model-based scenarios. It seeks to demystify and open up the coaching practise and provide tried, tested and solid ways for any coach to develop their skills. Packed full of essential core skills, plain facts and essential tips, tricks and advice all learnt from years of experience, it s simple to follow, easy to understand and everything is delivered in a friendly and very accessible way. As a method of training, directing and developing people, coaching continues to increase in popularity and is one of the most common tools used to help people improve their professional and private lives. At last, here s a book that strips away the usual complicated and unwieldy approaches and leaves just the golden nuggets, the insider knowledge and the real secrets of success; everything you really need to know to be the best coach you can be.
Creating the perfect coach/client relationship -- Set the scene -- Always work in three dimensions -- Look at what people do, not what they say -- Ask the killer questions : 'so what is stopping you?' -- Learn to push the pause button -- If the client doesn't know what good looks like, how will they know when they are there? -- There is only one coaching style : the one that works best for the client 9 listen and look for what's not being said -- If you do what you've always done : you will getwhat you've always got! -- Good coaches help people change : great coaches help the change stick -- Look back and learn -- And finally.
Print version record.
Includes index.
English.
Keywords: Employees -- Coaching of; Executive coaching; Personal coaching; Accompagnement de gestionnaires; Accompagnement (Psychologie); Employees -- Coaching of; Executive coaching; Personal coaching